Upaya Guru dalam Membentuk Kreativitas Siswa Kelas IV Berbasis Kerja Sama Melalui Daur Ulang Barang Bekas di Sekolah Dasar : Teachers' Efforts in Forming Creativity of Fourth Grade Students Based on Cooperation Through Recycling Used Goods in Elementary Schools - Sofi Oktalibriyanti; Ali Armadi; Muhammad Misbahudholam AR (ITScience (Information Technology and Science), 2025)
Creativity is an important aspect in the development of elementary school children that can be developed through collaborative learning. This study aims to analyze teachers' efforts in fostering creativity in grade IV students at SDN Paberasan II through collaborative recycling activities. This study uses a qualitative-descriptive approach with a case study design, where this approach was chosen to explore in depth the strategies and roles of teachers in fostering student creativity through collaborative activities that utilize recycled materials. This study also provides an overview and explanation of social phenomena in the school environment related to student creativity. The study results indicate that recycling activities designed and facilitated by teachers can encourage students to think creatively, develop ideas, and create innovative recycled products from used goods. In addition, this activity encourages cooperation between students in planning, making, and presenting works. Teachers play an active role as facilitators and motivators in creating a learning environment that supports creativity. The conclusion of this study shows that collaborative recycling activities are effective in increasing student creativity and fostering awareness of the importance of protecting the environment and honing problem-solving skills. Providing appreciation for students' work through school exhibition activities also provides intrinsic motivation that strengthens students' enthusiasm for learning and self-confidence.